Military operations from Kosovo to Kabul : the unique experiences of a combat lawyer - Nelson, James (Barnsley : Pen & Sword Military, 2021)
"In this highly unusual role for a lawyer, the author found himself in 1998 having to learn on his feet at a frightening pace as the newly promoted senior legal advisor to the charismatic General Sir Mike Jackson, the commander who led the Allied Rapid Reaction Corps into strife-torn Kosovo the following year to restore some sort of normality in the aftermath of the NATO bombing campaign.A peace deal was finally signed, only for Russia to intervene at the eleventh hour. The author was asked to provide rules of engagement for NATO to eject a stubborn Russian unit from Pristina by force, amongst fears of starting World War III, one of the few occasions when he thought perhaps civilian legal practice might not have been such a bad idea after all.Ten years later the author was back at HQ ARRC, promoted to Colonel. The culture shock on this occasion was not so much, spending six months in Afghanistan as being professionally embedded in a large American military legal office led by a hyper energetic US officer from the 'deep south'. Unlike the short, sharp Kosovo experience in central Europe, this war in central Asia was the longest in the history of the USA, although for the British it was just the latest in a succession of operations going back two centuries to the 'Great Game'.Trying to apply the law, balancing the need for aggression with compliance with Western notions of human rights, and vain efforts to win over the hearts and minds of a proud but impoverished people historically blighted by conflict proved to be unimaginably fraught.Military Operations From Kosovo to Kabul is one experienced soldier's fascinating account of these historic events, seen on the ground from the perspective of a legal professional, seldom associated with fighting wars."--
Includes bibliographical references.
Print version record.
WorldCat record variable field(s) change: 600, 610, 650
Keywords: Nelson, James; Great Britain. -- Army -- Officials and employees; Legal assistance to military personnel -- Great Britain; Electronic books